Evaluation of outcomes after coverage of exposed tibia with propeller-based perforator flaps - Sasmal, Manas; Das, Pritam; Seikh, Meheraj; Kumar, Naveen (International Surgery Journal, 2022)
Background: For small-and medium-sized soft-tissue defects in lower one third of leg without any degloving injury, the perforator propeller flaps are the authors preferred choice. With the study we shall present our experience with the use of three (tibio-peroneal system) perforator-based propeller flaps in the reconstruction of distal leg defects. Methods: A prospective study was conducted in the department of plastic and reconstructive surgery, over a period of 20 months from 1st January 2017 to 30th September 2018. All patients with small to large sized soft tissue defects affecting lower third of tibia were included in the study. Various findings were recorded and analyzed. Results: Among the affected areas that required coverage of soft tissues of the leg, in order of frequency, the middle third represented 15 cases (62.5%), and in the distal third 9 cases (37.5%). Flap dimensions ranged from 12 to 156 cm2, with an average size of 50 cm2. The flap rotation was 180 degrees in 19 cases (79.17%), 140 degrees in 3 cases (12.50%), and 160 degrees in 2 cases (8.33%). The flaps were based on a single perforating vessel of the posterior tibial artery in 12 cases (50%) of the cases; on the anterior tibial artery in 09 cases (37.5%), and in 3 cases (12.5%) the peroneal artery was chosen. Complications were present in 14% of the flaps. Conclusions: We concluded that the perforator-based propeller flaps are ideal in reconstructing small-medium defects of the middle and distal third of the leg.